Private companies: The missing link on the path to net zero - Alperen Gözlügöl; Wolf-Georg Ringe (Goethe University, Center for Advanced Studies on the Foundations of Law and Finance (LawFin), 2022)
Global consensus is growing on the contribution that corporations and finance must make towards the net-zero transition in line with the Paris Agreement goals. However, most efforts in legislative instruments as well as shareholder or stakeholder initiatives have ultimately focused on public companies. This article argues that such a focus falls short of providing a comprehensive approach to the problem of climate change. In doing so, it examines the contribution of private companies to climate change, the relevance of climate risks for them, as well as the phenomenon of brown-spinning (ie, the practice of public companies selling their highly polluting assets to private companies). We show that one cannot afford to ignore private companies in the net-zero transition and climate change adaptation. Yet, private companies lack several disciplining mechanisms that are available to public companies, such as institutional investor engagement, certain corporate governance arrangements, and transparency through regular disclosure obligations. At this stage, only some generic regulatory instruments such as carbon pricing and environmental regulation apply to them. The article closes with a discussion of the main policy implications. Primarily, we discuss and evaluate the recent push to extend climate-related disclosure requirements to private companies. These disclosures would not only help investors by addressing information asymmetry, but also serve a wide group of stakeholders and thus aim at promoting a transition to a greener economy.
Keywords: G38; K22; 330; private companies; net-zero transition; climate-related disclosures; brown-spinning; climate change; private equity